Peningkatan Nilai Tambah Kopi Gugeuls Melalui Teknologi Pasca Panen - Sukmawani, Reny; Rini, Neneng Kartika; Robiansyah, Anggi (AGRITEKH (Jurnal Agribisnis dan Teknologi Pangan), 2025)
This study evaluates the impact of post-harvest technology, specifically the use of roasting machines, on increasing the added value of Gugeuls coffee, a specialty product of Jatiroke Village, Jatinangor District, Sumedang Regency. Before the implementation of technology, Gugeuls coffee was traditionally processed, resulting in limited economic value. Using the Hayami method, this study calculated the added value from processing 50 kg of green beans into roasted beans. The findings revealed that the roasting machine provided an added value of IDR 117,600 per 50 kg of raw materials, reducing labor costs by up to 3%. Although the added value remained constant, the technology improved processing efficiency and reduced production costs. This positively impacted farmers' welfare and enhanced the competitiveness of local coffee products. This study highlights the importance of technological innovation in improving productivity and sustainability in agribusiness ventures.